2022
DOI: 10.1021/jacs.2c10606
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Inherently Chiral Calix[4]arenes via Palladium-Catalyzed Asymmetric Intramolecular C–H Arylations

Abstract: We report herein an efficient approach for the enantioselective synthesis of inherently chiral calix[4]arenes via palladium-catalyzed asymmetric intramolecular C−H arylations. Using a chiral bifunctional phosphine-carboxylate ligand, the inherent chirality on macrocyclic scaffolds was induced successfully, from which a wide range of calix [4]arenes with fluorenone motifs were obtained with good yields and excellent enantioselectivities (up to >99% ee). The synthetic utility of this method was demonstrated by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 64 publications
0
22
1
1
Order By: Relevance
“…As observed for calix [1]furan [2]pyrrole, [14] the ring expansion reaction of 1 proceeded in a regioselective fashion, with no evidence of other positional isomers being seen by NMR spectroscopy. However, in contrast to calix [3]pyrrole and calix [1]furan [2]pyrrole, which in our hands give calix [6]pyrrole-type macrocycles exclusively upon ring expansion, calix [1]furan [1]pyrrole [1]thiophene (1) was found to support formation of the calix [9]-and calix [12]pyrrole analogues 6 and 7. It thus appears to act as a useful synthetic precursor that allows access to large calix[n]pyrrole-type macrocycles that have…”
Section: Zuschriftencontrasting
confidence: 85%
See 3 more Smart Citations
“…As observed for calix [1]furan [2]pyrrole, [14] the ring expansion reaction of 1 proceeded in a regioselective fashion, with no evidence of other positional isomers being seen by NMR spectroscopy. However, in contrast to calix [3]pyrrole and calix [1]furan [2]pyrrole, which in our hands give calix [6]pyrrole-type macrocycles exclusively upon ring expansion, calix [1]furan [1]pyrrole [1]thiophene (1) was found to support formation of the calix [9]-and calix [12]pyrrole analogues 6 and 7. It thus appears to act as a useful synthetic precursor that allows access to large calix[n]pyrrole-type macrocycles that have…”
Section: Zuschriftencontrasting
confidence: 85%
“…In pioneering work, Wang and Tong synthesized chiral heteracalix[4]aromatics from achiral chains composed of four different aromatic rings with excellent enantioselectivity [8] . Very recently, Cai and co‐workers employed asymmetric functionalization to generate inherently chiral analogues of calix[4]arenes [9] . However, the design parameters [10] leading to inherently chiral macrocycles are not yet well‐established, in part because the energy barrier for ring inversion varies widely and in ways that are not always apparent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a sharp downfield (δ Η = 8.45 ppm for 1d) singlet was observed for the three N− H protons, consistent with a hydrogen-bonded environment. Taken together, these initial observations suggested that 1 and 2 possess a cyclic hydrogen-bonding network that enforces folding into a chiral, C 3 -symmetrical, bowl-shaped conformation (Figure 2c), 28,29 which must enantiomerize only slowly on the NMR timescale to preserve the four nonequivalent TACN proton environments.…”
Section: ■ Results and Discussionmentioning
confidence: 83%